Pelestarian Budaya Maritim Sumatera Selatan Ditinjau Dari Koleksi Fragmen Kapal di Museum Sriwijaya - Citra Ayu Virginia Pama; LR. Retno Susanti (LP4MK STKIP PGRI Lubuklinggau, 2026)
This research aims to optimize the role of museums as places to preserve the remaining local culture. This research aims to provide information on the study of the Sriwijaya Museum collection, namely wooden ship fragments, as well as the relationship of the Sriwijaya Museum in preserving cultural heritage. The ship fragment is proof of the maritime greatness of the Sriwijaya Chiefdom for the people of South Sumatra. The location of this research is at the Sriwijaya Museum, Palembang, in one of the collections, namely Remaining Ship Fragments. This ship fragment consists of the Ship Rudder, Ship Body, and Ship Directions. The Sriwijaya Museum has a role as an institution that protects the cultural heritage of the local community. One of them is maritime culture which is embedded in the lives of the people of South Sumatra. The research in this article uses descriptive qualitative methods resulting from analysis of previous scientific sources. The conclusion of this research shows that the Sriwijaya Museum has succeeded in becoming an institution that preserves cultural heritage in South Sumatra and provides a positive impact for the community.